Intakes of Vitamins and Minerals in Relation to Urinary Incontinence, Voiding, and Storage Symptoms in Women: A Cross-Sectional Analysis from the Boston Area Community Health Survey - Maserejian, Nancy N. (2011)
BACKGROUND: Whether lower urinary tract symptoms (LUTS), including voiding, storage, and urinary incontinence, are affected by dietary micronutrients is uncertain. OBJECTIVE: To test the hypothesis that carotenoid, vitamin C, zinc, and calcium intakes are associated with LUTS and urinary incontinence in women. DESIGN, SETTING, AND PARTICIPANTS: During an observational, cross-sectional, population-based epidemiologic study of 2060 women (30–79 yr of age) in the Boston Area Community Health (BACH) survey (2002–2005), data were collected by validated food frequency questionnaire and in-person interviews and analyzed using multivariate regression. MEASUREMENTS: LUTS, storage, and voiding symptoms were assessed using the American Urological Association Symptom Index (AUASI) and a validated severity index for urinary incontinence. RESULTS AND LIMITATIONS: Women who consumed high-dose vitamin C from diet and supplements were more likely to report storage symptoms, especially combined frequency and urgency (>500 vs <50 mg/d; odds ratio [OR]: 3.42; 95% confidence interval [CI], 1.44–8.12). However, greater consumption of dietary vitamin C or β-cryptoxanthin was inversely associated with voiding symptoms (p(trend) < 0.01). Both dietary and supplemental calcium were positively associated with storage symptoms (eg, supplement >1000 mg/d vs none; OR: 2.04; 95% CI, 1.35–3.09; p(trend) = 0.0002). No consistent associations were observed for β-carotene, lycopene, or other carotenoids, although smokers using β-carotene supplements were more likely to report storage problems. Whether the observed associations represent direct causes of diet on LUTS is uncertain. CONCLUSIONS: High-dose intakes of vitamin C and calcium were positively associated with urinary storage or incontinence, whereas vitamin C and β-cryptoxanthin from foods and beverages were inversely associated with voiding symptoms. Results indicate that micronutrient intakes may contribute to LUTS in dose-dependent and symptom-specific ways. Further study is needed to confirm these findings and their relevance to clinical treatment decisions.